ANALISIS STRUKTUR FISIK DAN STRUKTUR BATIN PADA LAGU GAYO “BERIJIN” - Saharani, Indah; Nuraina, Siti; Istiqamah, Istiqamah (Universitas Sultan Ageng Tirtayasa, 2024)
Literature is a form of human ideas that can be embodied in beauty. The form of writing that is sung is called song lyrics. Gayo Land is known as an area that gave birth to many artists and writers. Gayo songs have been part of the life of the Gayo people since ancient times, because the inhabitants of this cool area really like to sing. The purpose of this study is to analyze more deeply the physical structure and inner structure of the Gayo song